FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEN DAN RETURN SAHAM - Melisa Turnip, 10.05.51.0084 (Students Journal of Economic and Management, 2014)
This study aims about factors which influence dividend and stock return. The fundamental faktor which used in this study is return on asset, leverage, liquidity, dan size. This study sampled using a purposive sampling and obtain data for 134 samples. This study is free from the normality test and the classical assumption test. These result indicate that ROA has a positive and significant impact on DPR. Leverage has a positive but not significant impact on DPR. Liquidity has a positive and significant impact on DPR. Size has a positive but not significant impact on DPR. ROA has a positive but not significant impact on stock return. Leverage has a negative and not signficant impact on stock return. DPR has a negative and not significant impact on stock return. Liquidity has a negatve but significant impact on stock return. The latest results show that size has a positive but not significant impact on stock return. Key word: dividend, return saham, ROA, leverage, liquidity, and size